Temporal dynamics in biotic and functional recovery following mining. Issue 6 (19th April 2022) - Eldridge, David J.; Oliver, Ian; Powell, Jeff R.; Dorrough, Josh; Carrillo, Yolima; Nielsen, Uffe N.; Macdonald, Catriona A.; Wilson, Brian; Fyfe, Christine; Amarasinghe, Apsara; Kuginis, Laura; Peake, Travis; et al.
Abstract: Human‐induced disturbance has substantially influenced the structure and function of terrestrial ecosystems globally. However, the extent to which multiple ecosystem functions (multifunctionality) recover following anthropogenic disturbance (ecosystem recovery) remains poorly understood. We report on the first study examining the temporal dynamics in recovery of multifunctionality from 3 to 12 years after the commencement of rehabilitation following mining‐induced disturbance, and relate this information to changes in biota. We examined changes in 57 biotic (plants, microbial) and functional (soil) attributes associated with biodiversity and ecosystem services at four open‐cut coal mines in eastern Australia. Increasing time since commencement of rehabilitation was associated with increases in overall multifunctionality, soil microbial abundance, plant productivity, plant structure and soil stability, but not nutrient cycling, soil carbon sequestration nor soil nutrients. However, the temporal responses of individual ecosystem properties varied widely, from strongly positive (e.g. litter cover, fine and coarse frass, seed biomass, microbial and fungal biomass) to strongly negative (groundstorey foliage cover). We also show that sites with more developed biota tended to have greater ecosystem multifunctionality. Moreover, recovery of plant litter was closely associated with recovery of most microbial components, soil integrity and soil respiration. Overall, however, rehabilitated sites still differed from reference ecosystems a decade after commencement of rehabilitation. Synthesis and applications . The dominant role of plant and soil biota and litter cover in relation to functions associated with soil respiration, microbial function, soil integrity and C and N pools suggests that recovering biodiversity is a critically important priority in rehabilitation programs. Nonetheless, the slow recovery of most functions after a decade indicates that rehabilitation after open‐cut mining is likely to protracted. Abstract : The dominant role of plant and soil biota and litter cover in relation to functions associated with soil respiration, microbial function, soil integrity and C and N pools suggests that recovering biodiversity is a critically important priority in rehabilitation programs. Nonetheless, the slow recovery of most functions after a decade indicates that rehabilitation after open‐cut mining is likely to protracted.